2020
DOI: 10.3390/ijerph17155499
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Work Conditions and Associations with Workers’ Health in Recent 15 Years: The Role of Job Automation Probability

Abstract: Job automation and associated psychosocial hazards are emerging workplace challenges. This study examined the trends in work conditions and associations with workers’ health over time in jobs with different automation probabilities. We utilized data from six waves of national questionnaire surveys of randomly selected 95,762 employees between 2001 and 2016. The Job Content Questionnaire, the Copenhagen Burnout Inventory, and the Self-Rated Health Scale were applied, and working time was self-reported. Automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
(49 reference statements)
0
3
1
Order By: Relevance
“…Our study findings are also novel in that it is contrary to previous studies showing that occupations with high automation risk are related to a decrease in burnout and job stress [ 16 , 17 ], which are well-known factors causing sleep disorders [ 33 , 41 ]. As Cheng et al suggested, these previous results may be attributable to the exposure of workers in occupations with high automation risk to lower occupation-related emotional demands.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Our study findings are also novel in that it is contrary to previous studies showing that occupations with high automation risk are related to a decrease in burnout and job stress [ 16 , 17 ], which are well-known factors causing sleep disorders [ 33 , 41 ]. As Cheng et al suggested, these previous results may be attributable to the exposure of workers in occupations with high automation risk to lower occupation-related emotional demands.…”
Section: Discussioncontrasting
confidence: 89%
“…A different group of studies has explored various health conditions of workers in occupations with high probabilities of being replaced by automation. Workers in occupations vulnerable to technological replacement are associated with poor overall health [ 16 , 17 ], work-related injury or disease [ 35 ], and increased disability and mortality risk [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations